Characterization and potential applications of a recombinant antifreeze protein from an antarctic yeast Glaciozyma antarctica produced in Pichia pastoris - Md Tab M.,; Hashim N.H.F.,; Abu Bakar F.D.,; Illias R.,; Najimudin N.,; Mahadi N.M.,; Murad A.M.A., (Penerbit Universiti Kebangsaan Malaysia, 2017)
Ice recrystallization during thawing post-cryopreservation results in extensive cellular damage and ultimately leads to cell death and reduced cell viability. Antifreeze proteins (AFPs) are a group of proteins that allow organisms to survive in subzero environments. These proteins have thermal hysteresis and ice recrystallization inhibitory activities. In this present study, we demonstrated the efficiency of a recombinant antifreeze protein from the Antarctic yeast, Glaciozyma antarctica, as a recrystallization inhibitor (RI) of ice growth and assessed its application as a cryopreservative of the fungal cutinase enzyme against freeze-thaw cycles. Recombinant Afp1 from G. antarctica, a psychrophilic yeast, has been produced in a methylotrophic yeast, Pichia pastoris, system that results in the expression of a hyper-glycoprotein (~55 kDa). Recombinant Afp1 exhibits antifreeze functions: thermal hysteresis (TH) and recrystallization inhibition where the highest TH values recorded for ~0.5°C at 10 mg/mL. The cryoprotective effects of Afp1 on purified recombinant cutinase showed that Afp1 can retain enzymatic activity up to ~20% when subjected to several cycles of freeze thawing. These findings indicate that Afp1 might act as a cryoprotective agent and thus, has great potential in biotechnology applications.